Peran Pesantren Darunnajah Jakarta Dalam Pendidikan Karakter Santri Melalui Pembelajaran Bahasa Arab - Azmi Islami (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2025)
This descriptive qualitative study aims to examine the role of Darunnajah Islamic Boarding School in Jakarta in shaping the character of its students through Arabic language learning. Data collected through in-depth interviews, participatory observations, and document analysis. The findings show that Darunnajah Islamic Boarding School plays a significant role in character development, especially through Arabic language learning, which focuses not only on linguistic skills but also on instilling character values such as honesty, discipline, and social awareness. The teaching methods used, such as muhadatsah, improve students' communication skills while also strengthening their character. However, challenges faced including the influence of technology and globalization, require adaptive strategies that maintain Islamic values. Suggestion, enhancing teacher professionalism, maximizing technology use, as well as innovating the curriculum and extracurricular activities based on Arabic to improve students' character.